Perlindungan Hukum Terhadap Anak sebagai Korban Tindak Pidana Asusila (Studi Putusan No.398/Pid.Sus/2018/PN.Mdn) - Abdul Aziz P Nasution; Ridho Mubarak; Anggreni Atmei Lubis (Universitas Medan Area, 2021)
Child Protection means all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and protection from violence and discrimination. This type of research is normative juridical and the nature of the research is descriptive-analytical. The form of legal protection for children as victims of immoral crime is by protecting and prioritizing the interests of children as victims, prioritizing recovery and protection of children through educational efforts on reproductive health, religious values and moral values, social rehabilitation, psychosocial assistance during treatment to recovery and provision. protection and assistance at every examination starting from investigation, prosecution to examination in court. The judge's consideration in giving punishment to perpetrators of immoral crimes in decision No.398 / Pid.Sus / 2018 / PN.Mdn is that the defendant's actions are disturbing to the public, that the defendant's actions have ruined the future of the child victim Intan Fitria and consider mitigating things, that the defendant has never been convicted, that the defendant acknowledged and regretted his actions, that the defendant was polite in court and the defendant would not repeat his actions. Efforts to tackle immoral crimes against minors are to supervise children, pay attention to their environment and friends, and educate and instill religious values and knowledge about sexuality at an early age.